Tackling hepatocellular carcinoma with individual or combinatorial immunotherapy approaches. (31st March 2020) - Tagliamonte, Maria; Mauriello, Angela; Cavalluzzo, Beatrice; Ragone, Concetta; Manolio, Carmen; Petrizzo, Annacarmen; Buonaguro, Luigi
Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of death from cancer globally. Indeed, there is a single drug approved as first-line systemic therapy in advanced unresectable HCC, providing a very limited survival benefit. In earlier stages, 5-year survival rates after surgical and loco-regional therapies are extremely variable depending on the stage of disease. Nevertheless, HCC is considered an immunogenic tumor arising in chronically inflamed livers. In such a scenario, immunotherapy strategies for HCC, in particular combinations including cancer vaccines, may represent a key therapeutic tool to improve clinical outcome in HCC patients. However, a lot of improvement is needed given the disappointing results obtained so far. Highlights: Besides surgical and loco-regional interventions, Sorafenib is the only systemic drug is approved as first line treatment in inoperable HCC patients. Anti-PD-1 has proven efficacy only as second line systemic therapy in patiens who failed to Sorafenib.. Results from few clinical trials evaluating adoptive T cell therapy are awaited. Cancer vaccines are currently developed and evaluated in clinical trials based on new TAAs as well as personalized mutated neoantigens. Expanding observations on all these strategies individually and in combination, will be the main path for improving clinical outcome in HCC.